2014
DOI: 10.1055/s-0034-1379253
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Thioalkyne-Substituted Thiazolidine-2-thiones Using Tris(tri­methylsilyl)methyllithium and Carbon Disulfide

Abstract: An efficient, environmentally benign, and simple one-pot approach to the synthesis of 5-(iodomethyl)thiazolidine-2-thiones via multicomponent reaction of allylamines, carbon disulfide, and iodine under solvent-free conditions is presented. The obtained 5-(iodomethyl)thiazolidine-2-thiones were converted into silyl-protected terminal [(ethynylthio)methyl]-substituted thiazolidine-2-thiones by treatment with lithium 2,2,2-tris(trimethylsilyl)ethanedithioate, produced by the reaction of tris(trimethylsilyl)methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The C-atom signals corresponding to C=S of thiazolidine-2-thione rings observed in the region of 193-195 ppm. The thiazolidine-2-thiones containing 1,2,3-triazoles group 3(a˗g) were tested for their in vitro antibacterial activity by the disc diffusion method 33 , the data are listed in Table 5. As shown in Table 5, it has been found that compounds 3c, 3d and 3g possess different inhibitory activities against both gram-positive (Staphylococcus aureus) and gram-negative (Escherichia coli) bacterium (Table 5, entries 3, 4, and 7), while compound 3f showed moderate inhibitory activity against Escherichia coli bacteria (Table 5, entry 6).…”
Section: Resultsmentioning
confidence: 99%
“…The C-atom signals corresponding to C=S of thiazolidine-2-thione rings observed in the region of 193-195 ppm. The thiazolidine-2-thiones containing 1,2,3-triazoles group 3(a˗g) were tested for their in vitro antibacterial activity by the disc diffusion method 33 , the data are listed in Table 5. As shown in Table 5, it has been found that compounds 3c, 3d and 3g possess different inhibitory activities against both gram-positive (Staphylococcus aureus) and gram-negative (Escherichia coli) bacterium (Table 5, entries 3, 4, and 7), while compound 3f showed moderate inhibitory activity against Escherichia coli bacteria (Table 5, entry 6).…”
Section: Resultsmentioning
confidence: 99%
“…Terminal alkenes are well tolerated in this regiospecific iodocyclization giving 3.1 , while the employment of cinnamylamine affords no product. Safa and Alyari 3b reported a similar transformation using K 2 CO 3 under solvent-free conditions.…”
Section: Reactions With Electrophilesmentioning
confidence: 83%
“…In 2015, 5‐(iodomethyl)thiazolidine‐2‐thiones were produced in high yields by the K 2 CO 3 ‐catalyzed multicomponent reaction under solvent‐free conditions (Scheme 20). [51] Synthestic protocol was optimized through several reaction factors such as the mole ratio of substrate, type of solvent, amount of catalyst, and reaction time. It was observed that 1 : 3 : 4 ratio of N‐benzylallylamine/carbon disulfide/iodine was better in presence of K 2 CO 3 (0.5 equiv.)…”
Section: Heterocyclic Compoundsmentioning
confidence: 99%